INTEGRATING TECHNOLOGY AND INNOVATIVE PEDAGOGIES IN PHONETIC EDUCATION: A SYSTEMATIC LITERATURE REVIEW - Indriyani (Universitas Negeri Surabaya, 2023)
Phonetics, a crucial subfield of linguistics, has seen substantial advancements, particularly in educational contexts. This systematic literature review aims to identify and synthesize emerging trends in phonetics research from 2019 to 2024, focusing on acoustic and articulatory phonetics, phonetic ear-training, and the use of technological tools in teaching. By examining 15 key studies from an initial pool of Utilizing tools like Publish or Perish, with database crossreff (1000) and google schooler (500) and total 1500 (n=15) studies to explore how orthographic inputs affect L2 learners' speech perception, production, phonological awareness, and lexical learning.this review highlights significant advancements such as Communicative Pronunciation Teaching (CPT) and network-based learning modes, which have shown to enhance phonetic instruction effectively. However, challenges remain, including the variability in access to technology and limited research on the long-term impacts of phonetic training. The findings suggest that integrating innovative pedagogical approaches with technological tools can significantly improve phonetic education, thereby enhancing language learning outcomes. This study underscores the importance of personalized teaching strategies and the need for further research into the long-term effects of phonetic training, aiming to contribute to the development of more effective and accessible phonetic learning methods. The implications of this research extend beyond phonetics, suggesting that similar integrative approaches could be beneficial in other areas of language education, thus promoting better educational outcomes on a larger scale.